1980
DOI: 10.1080/00926238008406082
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Therapy For The Post Coronary Patient

Abstract: This paper examines the theory and research on the subject of sexual activity post myocardial infarction. An etiological model of sexual dysfunction following MI is presented, treatment implications from the model are discussed, and a treatment program with specific interventions is discussed. Extensions of the conceptual model and treatment outline result in a format for feasible "preventative" therapy implemented immediately following the cardiac event. Emphasis is placed on the systemic etiology and effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1985
1985
2017
2017

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…[43] reported that the patients with a penile brachial pressure index (PBPI) of 0.65 or less had a significantly greater risk of a MI or a cerebrovascular accident than patients with higher PBPIs. But most of the experts [44–47] considered ED as a complication or late consequence of MI at that time. Our analysis indicated that compared with healthy subjects, the subjects with ED had an overall RR 1.43 time developing MI.…”
Section: Discussionmentioning
confidence: 99%
“…[43] reported that the patients with a penile brachial pressure index (PBPI) of 0.65 or less had a significantly greater risk of a MI or a cerebrovascular accident than patients with higher PBPIs. But most of the experts [44–47] considered ED as a complication or late consequence of MI at that time. Our analysis indicated that compared with healthy subjects, the subjects with ED had an overall RR 1.43 time developing MI.…”
Section: Discussionmentioning
confidence: 99%
“…Hospital rates are highest among divorced, separated and widowed individuals Some Prospects for Couples Therapy 145 (Segraves, 1980). Numerous studies have investigated the relationship between psychiatric disturbance and marital relationships (Birchnell & Kennard, 1983;Bullock, 1972;Collins et al, 1971;Hinchliffe et al, 1978;Kreitman et al, 1971;Pattern & Waring, 1984;Weissman & Paykel, 1974).…”
Section: Marriage and Mental Healthmentioning
confidence: 96%
“…Another surgical group that has received attention in relation to post-operative marital and sexual functioning are patients who have undergone coronary bypass surgery (Althof et al, 1984;Thurer, 1982;Waxberg, 1979) or who have recovered from coronaries (Hellerstein & Friedman, 1969;Sanders & Sprenkle, 1980;Scalzi & Dracup, 1978;Tuttle et al, 1964). Althof et al (1984) investigated the effects of coronary bypass on female sexual, psychological and vocational adaption.…”
Section: Radical Surgerymentioning
confidence: 97%